Graffiti on the Walls of Institutions of Palestinian Higher Education: Motives and Behavior - Aljibrine, Majed Khaleel; Abu-Zunied, Samir Ahmad (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to identify the motives and behavior standing behind writing on the walls of institutions of higher education from the point of view of university students in Hebron Governorate. The researchers used the descriptive exploratory approach and the qualitative method through the structured interviewing tool. They developed a scale consisting of (19) items. Respondents asked to identify and order the most important (10) items from their own perspectives. The population of the study consists of (21813) subjects, the total of students according to official statistics issued in the second semester of the academic year (2019-2018) from the four universities in Hebron Governorate: Palestine Polytechnic University, Hebron University, Al Quds Open University with its three branches (Hebron, Yatta and Dura), and Palestine Technical University (PTU) Al- Aroub Branch. For the purpose of the study, a simple random sample of 679 students selected. The outcome of the study concluded that respondents identified and ordered the most important (10) items. They indicated that the "Psychological factor or drive", item 1, is the most important one, and (the motive of rumor, deception and dissemination of lies), item 7, is the last one while the (economic motive), item 19, is the least drive. In light of these results, the researchers present some useful recommendations. Forming expert committees at the universities is badly needed. Committees should be entitled with certain duties as: observing the writings of the students on the walls of the Palestinian higher education institutions, understanding their contents, identifying the needs of students, educating students about the importance of preserving university property, and prohibiting writing on its walls.
Keywords: graffiti; bathroom; rest house